Diffusion modeling and intelligence: drift rates show both domain-general and domain-specific relations with intelligence - Lerche, Veronika; Krause, Mischa von; Voß, Andreas; Frischkorn, Gidon T.; Schubert, Anna-Lena; Hagemann, Dirk (Journal of experimental psychology, 2020)
APA PsycNet DoiLanding page